Comparison of Coronavirus Disease Severity Using National Early Warning Score in Vaccinated versus Unvaccinated Patients Against COVID-19 Presenting to the Emergency Department - Inayat, Alisha; Khan, Abdus Salam; Sheikh, Assad Kamal; Asim, Maheen (Biological and Clinical Sciences Research Journal, 2025)
Coronavirus disease severity varies widely at presentation, and early risk stratification in emergency settings is essential for timely management. The National Early Warning Score is a validated tool for assessing clinical deterioration. Objective: To determine coronavirus disease severity using the National Early Warning Score and to compare disease severity between vaccinated and unvaccinated patients presenting to the emergency department. Methods: This descriptive cross-sectional study was conducted at the Emergency Department of Shifa International Hospital, Islamabad. A total of 95 laboratory-confirmed patients with coronavirus disease presenting to the emergency department were enrolled. Patients were categorised into two groups: fully vaccinated against coronavirus disease and unvaccinated. Vaccination status was verified through patient or family confirmation using the NADRA coronavirus disease vaccination certificate. National Early Warning Score values and demographic and clinical variables were recorded. Data were analysed using SPSS, and comparisons between groups were performed, with p-values of 0.05 or less considered statistically significant. Results: The mean age of the participants was 60.78 ± 16.97 years, with 54 patients aged between 50 and 75 years. Males comprised 57.9 percent of the study population. The overall mean National Early Warning Score was 4.55 ± 3.04. Low, moderate, and high risk scores were observed in 49.5 percent, 27.4 percent, and 23.2 percent of patients, respectively. Vaccinated individuals constituted 73.7 percent of the cohort. The mean National Early Warning Score was significantly lower in vaccinated patients compared to unvaccinated patients (3.53 ± 2.62 vs 7.40 ± 2.22, p < 0.0001). High risk scores were observed in 64 percent of unvaccinated patients compared to 8.6 percent of vaccinated patients, demonstrating a highly significant association (p < 0.0001). Conclusion: Unvaccinated patients presenting with coronavirus disease have a significantly higher risk of severe illness compared to vaccinated patients. Vaccination is strongly associated with reduced disease severity as assessed by the National Early Warning Score.